A sperator for an electrochemical device and an electrochemical device comprising the same

KR103021710B1Active Publication Date: 2026-09-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020240057579
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-26
Filing Date
2024-04-30
Publication Date
2026-09-18
Estimated Expiration
2044-04-30

Smart Images

  • Figure 112024047343685-PAT00001_ABST
    Figure 112024047343685-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for an electrochemical device and an electrochemical device including the same. Specifically, it relates to a separator for an electrochemical device and an electrochemical device including the same that can reduce short circuit failure rates and low voltage failure rates by controlling the surface roughness of a coating layer and the size ratio of particles included in the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2023-0068199 filed with the Korean Intellectual Property Office on May 26, 2023, the entire contents of which are incorporated into the present invention. The present invention relates to a separator for an electrochemical device and an electrochemical device including the same, and specifically, to a separator for an electrochemical device and an electrochemical device including the same that can reduce short circuit failure rates and low voltage failure rates by controlling the surface roughness of a coating layer and the size ratio of particles included in said coating layer. Background Technology

[0002] Among the components of an electrochemical device, the separator comprises a porous polymer substrate located between the anode and cathode. It serves to isolate the anode and cathode, prevent electrical short circuits between the two electrodes, and allow the passage of electrolytes and ions. Although the separator itself does not participate in electrochemical reactions, its physical properties, such as wettability to the electrolyte, degree of porosity, and thermal shrinkage rate, affect the performance and safety of the electrochemical device.

[0003] Accordingly, various methods are being attempted to modify the physical properties of a coating layer by adding a coating layer to a porous polymer substrate to enhance the physical properties of the separation membrane, and by adding various materials to the coating layer. For example, inorganic materials may be added to the coating layer to improve the mechanical strength of the separation membrane, or inorganic materials or hydrates may be added to the coating layer to improve the flame retardancy and heat resistance of the polymer substrate.

[0004] The separator can be bonded to the electrode through a lamination process, and to ensure adhesion between the electrode and the separator, a binder resin can be added to the coating layer composition of the separator.

[0005] Meanwhile, in the process of manufacturing electrode assemblies, there is a lamination process in which high temperature and pressure are applied to bond the electrode and the separator. This process had the problem of the separator being damaged by the pressure and temperature. In the case of separators forming a coating layer using the conventional phase inversion method, the binder was not evenly distributed on the surface, resulting in the formation of areas with high and low binder content, thereby forming a non-uniform coating layer.

[0006] Furthermore, in the case of a separator with a non-uniform coating layer, when high pressure is applied, the pressure is not applied evenly to the entire separator, causing damage to the separator and resulting in a decrease in dielectric breakdown voltage.

[0007] Therefore, research was needed on a membrane capable of applying pressure evenly across the entire membrane by including a uniform coating layer. The problem to be solved

[0008] The technical problem that the present invention aims to solve is to provide a separator for an electrochemical device and an electrochemical device including the same, which can prevent damage to the separator caused by excessive concentration of pressure applied in a part of the separator during the process of manufacturing a secondary battery in which an electrode and a separator are laminated, and prevent the dielectric breakdown voltage from being lowered.

[0009] However, the problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0010] One embodiment of the present invention comprises a porous polymer substrate; and a coating layer provided on at least one surface of the porous polymer substrate and comprising a particulate first polymer binder, a second polymer binder, and inorganic particles, wherein the average particle size (D) of the first polymer binder 50) and the average particle size (D) of the above inorganic particles 50 The ratio of ) is 1:0.5 to 1:5, and the weight of the first polymer binder included in the coating layer is greater than the weight of the second polymer binder, thereby providing a separator for an electrochemical device.

[0011] According to one embodiment of the present invention, the surface roughness (Sa) of the surface opposite to the side adjacent to the porous polymer substrate of the coating layer may be 0.20 μm or less.

[0012] According to one embodiment of the present invention, the first polymer binder may comprise one selected from an acrylic binder, a polyvinylidene binder, and a combination thereof.

[0013] According to one embodiment of the present invention, the second polymer binder may be one selected from the group consisting of polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylamide (PAM), and combinations thereof.

[0014] According to one embodiment of the present invention, the average particle size (D) of the first polymer binder 50 ) may be 200 nm or more and 450 nm or less.

[0015] According to one embodiment of the present invention, the average particle size (D) of the inorganic particles 50 ) may be 300 nm or more and 700 nm or less.

[0016] According to one embodiment of the present invention, the weight ratio of the first polymer binder and the second polymer binder may be 5.5:4.5 to 9.5:0.5.

[0017] According to one embodiment of the present invention, the total content of the first polymer binder and the second polymer binder may be 5 parts by weight or more and 30 parts by weight or less per 100 parts by weight of the coating layer.

[0018] According to one embodiment of the present invention, when pressurized for 10 seconds under conditions of 70°C and 5.2 MPa, the rate of change in thickness of the coating layer defined by the following mathematical formula 1 may be 10% or more and 25% or less.

[0019] [Mathematical Formula 1]

[0020] Thickness change rate = (Thickness of coating layer before pressurization - Thickness of separator after pressurization) / Thickness of coating layer before pressurization

[0021] According to one embodiment of the present invention, when impregnated for 24 hours under conditions of 25°C and 1 atmosphere in a solution comprising 70 parts by volume of ethylene carbonate and 30 parts by volume of ethylmethyl carbonate, the rate of change in the porosity of the coating layer defined by the following mathematical formula 2 may be 10% or more and 20% or less.

[0022] [Mathematical Formula 2]

[0023] Rate of change in porosity = (Porosity of coating layer after impregnation - Porosity of coating layer before impregnation) / Porosity of coating layer before impregnation

[0024] One embodiment of the present invention provides an electrochemical device comprising: an anode; a cathode; and a separator interposed between the anode and the cathode. Effects of the invention

[0025] A separator for an electrochemical device according to one embodiment of the present invention allows pressure applied during the lamination process of combining the electrode and the separator to be applied uniformly to the separator, and can improve the dielectric breakdown voltage.

[0026] A separator for an electrochemical device according to one embodiment of the present invention can prevent damage to a porous polymer substrate, reduce local changes in the separator, and reduce the short circuit failure rate.

[0027] A separator for an electrochemical device according to one embodiment of the present invention includes a particulate polymer binder to buffer the pressure applied in the lamination process, and includes a polymer binder that dissolves in an electrolyte to increase the porosity of the coating layer, thereby enabling it to buffer the pressure applied in the jig formation (j / f) process.

[0028] An electrochemical device according to one embodiment of the present invention can reduce the short circuit failure rate and the low voltage failure rate, and can improve the dielectric breakdown voltage. Brief explanation of the drawing

[0029] FIG. 1 is a schematic diagram of a separator for an electrochemical device according to one embodiment of the present invention. FIG. 2 is a schematic diagram of an electrochemical element according to one embodiment of the present invention. Specific details for implementing the invention

[0030] In this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0031] In this specification, "A and / or B" means "A and B, or A or B".

[0032] In this specification, when a component is described as being "on" one component, this means that, unless specifically stated otherwise, other components may be placed in between, without excluding the placement of other components.

[0033] In this specification, the characteristic of “having pores” means that a gaseous and / or liquid fluid can pass from one side to the other side of the object through a structure in which the object includes a plurality of pores and said pores are interconnected.

[0034] In the present specification, the separator has porous characteristics including a plurality of pores and acts as a porous ion-conducting barrier that blocks electrical contact between the cathode and the anode in an electrochemical device while allowing ions to pass through.

[0035] The present invention will be described in more detail below.

[0036] One embodiment of the present invention comprises a porous polymer substrate (110); and a coating layer (130) provided on at least one surface of the porous polymer substrate (110) and comprising a particulate first polymer binder, a second polymer binder, and inorganic particles, wherein the average particle size (D) of the first polymer binder 50 ) and the average particle size (D) of the above inorganic particles 50 The ratio of ) is 1:0.5 to 1:5, and the weight of the first polymer binder included in the coating layer (130) is greater than the weight of the second polymer binder, thereby providing a separator (100) for an electrochemical device.

[0037] A separator for an electrochemical device according to one embodiment of the present invention ensures that pressure applied during the lamination process of combining the electrode and the separator is applied uniformly to the separator, and can improve the dielectric breakdown voltage. Furthermore, a separator for an electrochemical device according to one embodiment of the present invention prevents damage to the porous polymer substrate, reduces local changes in the separator, and reduces the short-circuit failure rate. In addition, a separator for an electrochemical device according to one embodiment of the present invention includes a particulate polymer binder to buffer the pressure applied during the lamination process, and includes a polymer binder that dissolves in the electrolyte to increase the porosity of the coating layer, thereby buffering the pressure applied during the jig formation (j / f) process.

[0038] FIG. 1 is a schematic diagram of a separator (100) for an electrochemical device according to one embodiment of the present invention. With reference to FIG. 1, a separator for an electrochemical device according to one embodiment of the present invention will be described in detail.

[0039] According to one embodiment of the present invention, the separator for the electrochemical device comprises a porous polymer substrate (110). As described above, by including the porous polymer substrate, the separator for the electrochemical device allows lithium ions to pass through while blocking electrical contact, and enables a shutdown function at an appropriate temperature.

[0040] According to one embodiment of the present invention, the porous polymer substrate may be manufactured using a polyolefin resin as a base resin. Examples of polyolefin resins include polyethylene, polypropylene, and polypentene, and may include one or more of these. A porous separator, i.e., having a plurality of pores, manufactured using such a polyolefin resin as a base resin, can provide a shutdown function at an appropriate temperature.

[0041] According to one embodiment of the present invention, the weight-average molecular weight of the polyolefin resin may be 500,000 or more and 1,500,000 or less. By controlling the weight-average molecular weight of the polyolefin resin within the above-described range, the compression resistance of the separator can be improved. Furthermore, when using a mixture of different types of polyolefin resins or forming a separator with a multilayer structure made of different types of polyolefin resins, the weight-average molecular weight of the polyolefin resins can be calculated by adding the weight-average molecular weights according to the content ratio of each polyolefin resin.

[0042] In one embodiment of the present invention, the weight-average molecular weight (Mw) can be measured by gel permeation chromatography (GPC: gel permeation chromatography, PL GPC220, Agilent Technologies), and the measurement conditions can be set as follows.

[0043] - Column: PL Olexis (Polymer Laboratories)

[0044] - Solvent: TCB (Trichlorobenzene)

[0045] - Flow rate: 1.0 ml / min

[0046] - Sample concentration: 1.0 mg / ml

[0047] - Injection volume: 200 µl

[0048] - Column temperature: 160 ℃

[0049] - Detector: Agilent High Temperature RI detector

[0050] - Standard: Polystyrene (corrected by a cubic function)

[0051] According to one embodiment of the present invention, the porous polymer substrate may be manufactured by a method (wet method) in which a polyolefin-based resin is kneaded with a plasticizer (diluent) at a high temperature to form a single phase, the polymer material and the plasticizer are phase-separated during the cooling process, the plasticizer is extracted to form pores, and then stretched and heat-set. Additionally, the porous polymer substrate using a polyolefin-based resin may comprise a core portion made of a mixture of polyethylene and polypropylene and a polyethylene skin portion laminated on both sides of the core portion.

[0052] According to one embodiment of the present invention, the average pore size and the maximum pore size of the separation membrane can be easily manufactured by a person skilled in the art to meet the scope of the present invention by adjusting the mixing ratio of the plasticizer, the stretching ratio, and the heat-setting treatment temperature.

[0053] According to one embodiment of the present invention, the separator (100) for an electrochemical device comprises a coating layer (130) provided on at least one surface of the porous polymer substrate (110). Specifically, the separator for an electrochemical device comprises a coating layer provided on one or both surfaces of the porous polymer substrate. As described above, by including a coating layer provided on at least one surface of the porous polymer substrate, the heat resistance of the separator is improved, mechanical properties are improved, and the separator shrinks at high temperatures, thereby preventing an electrical short circuit of the electrode.

[0054] According to one embodiment of the present invention, the coating layer comprises a particulate first polymer binder, a second polymer binder, and inorganic particles. As described above, by including the particulate first polymer binder, the second polymer binder, and the inorganic particles in the coating layer, the heat resistance of the separator is improved, mechanical properties are improved, the separator shrinks at high temperatures to prevent electrical short circuits in the electrodes, and pores can be formed within the coating layer.

[0055] According to one embodiment of the present invention, the coating layer may be formed by binding the inorganic particles to the particle-shaped first polymer binder particles and the second polymer binder and accumulating them within the side. Alternatively, the coating layer may be formed by binding the inorganic particles to the particle-shaped first polymer binder particles and accumulating them within the side. The pores within the coating layer may originate from the interstitial volume, which is the empty space between the inorganic particles.

[0056] In one embodiment of the present invention, the porosity of the coating layer may be 30 volume% to 70 volume%. If the porosity is 70 volume% or less, mechanical properties capable of withstanding a press process for bonding with an electrode can be secured, and the surface opening ratio does not become too high, making it suitable for securing adhesion. On the other hand, if the porosity is 30 volume% or more, it is advantageous in terms of ion permeability.

[0057] In this specification, the term porosity refers to the ratio of the volume occupied by pores to the total volume, and uses volume % as its unit; it may be used interchangeably with terms such as porosity and porosity.

[0058] In this specification, porosity corresponds to a value obtained by subtracting the volume converted into the weight and density of each component of the coating layer from the volume calculated in terms of the thickness, width, and length of the coating layer.

[0059] In one embodiment of the present invention, the porosity and pore size of the coating layer can be measured by the BET 6-point method using the nitrogen gas adsorption flow method with scanning electron microscope (SEM) images, a mercury porosimeter, a capillary flow pore distribution analyzer, or a porosimetry analyzer (Bell Japan Inc, Belsorp-II mini). In this case, it may be advantageous to use a capillary flow pore distribution analyzer.

[0060] According to one embodiment of the present invention, the thickness of the coating layer may be formed to a thickness of 1 μm to 20 μm on either side of the porous polygonal substrate, but is not particularly limited thereto. The thickness can be adjusted to an appropriate range by a person skilled in the art in terms of heat resistance or electrical resistance.

[0061] In one embodiment of the present invention, the thickness of the polymer substrate and / or the coating layer, etc., can be measured by applying a contact-type thickness gauge. For example, the contact-type thickness gauge may use the VL-50S-B from Mitutoyo.

[0062] According to one embodiment of the present invention, the average particle size (D) of the first polymer binder in the coating layer 50 ) and the average particle size (D) of the above inorganic particles 50 The ratio of ) is 1:1.0 to 1:5. Specifically, the average particle size (D) of the first polymer binder in the coating layer 50 ) and the average particle size (D) of the above inorganic particles 50The ratio of ) may be 1:1.0 to 1:4.5, 1:1.5 to 1:4.0, 1:2.0 to 1:3.5, or 1:2.5 to 1:3.0. Preferably, the average particle size (D) of the first polymer binder in the coating layer is 50 ) and the average particle size (D) of the above inorganic particles 50 The ratio of ) may be 1:1.0 to 1:3.0. Within the above-described range, the average particle size (D) of the first polymer binder of the coating layer 50 ) and the average particle size (D) of the above inorganic particles 50 By adjusting the ratio of ), the surface roughness (Sa), i.e., the roughness of the coating layer surface can be controlled, and by reducing the surface roughness, the dielectric breakdown voltage can be improved by preventing excessive pressure from being applied to specific parts even when pressure is applied. Furthermore, the average particle size (D) of the first polymer binder in the coating layer 50 ) and the average particle size (D) of the above inorganic particles 50 By adjusting the ratio of ), the first polymer binder can migrate to the surface of the coating layer to reduce the surface roughness.

[0063] In this specification, "D 50 "Particle size" refers to the particle size at the 50% point of the cumulative distribution of particle numbers according to particle size. The above particle size can be measured using the laser diffraction method. Specifically, after dispersing the powder to be measured in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in diffraction patterns according to particle size is measured as the particles pass through the laser beam to calculate the particle size distribution. By calculating the particle diameter at the point where the cumulative distribution of particle numbers according to particle size in the measuring device reaches 50%, D 50 Particle size can be measured.

[0064] According to one embodiment of the present invention, the second polymer binder may be a soluble polymer binder. Specifically, a soluble polymer binder may mean that it is dissolved by an electrolyte. That is, the soluble polymer binder may be dissolved and eluted by the electrolyte. As described above, by selecting the second polymer binder as a soluble polymer binder, the porosity of the coating layer in the electrochemical device injected with the electrolyte increases to 10% or more and 20% or less, thereby enabling a buffering effect against the pressure applied in the jig formation process.

[0065] According to one embodiment of the present invention, the weight of the first polymer binder included in the coating layer is greater than the weight of the second polymer binder. By implementing the weight of the first polymer binder included in the coating layer as greater than the weight of the second polymer binder as described above, the porosity of the coating layer is prevented from increasing excessively, and the binding strength of the coating layer can be increased.

[0066] According to one embodiment of the present invention, the surface roughness (Sa) of the surface opposite to the side adjacent to the porous polymer substrate of the coating layer may be 0.20 μm or less. Specifically, the surface roughness (Sa) of the surface opposite to the side adjacent to the porous polymer substrate of the coating layer may be 0 μm or more and 0.20 μm or less, greater than 0 μm and 0.19 μm or less, 0.1 μm or more and 0.18 μm or less, 0.2 μm or more and 0.17 μm or less, 0.3 μm or more and 0.16 μm or less, 0.4 μm or more and 0.15 μm or less, 0.5 μm or more and 0.14 μm or less, 0.6 μm or more and 0.13 μm or less, 0.7 μm or more and 0.12 μm or less, 0.8 μm or more and 0.11 μm or less, or 0.9 μm or more and 0.10 μm or less. By controlling the surface roughness (Sa, area roughness) of the surface opposite to the side adjacent to the porous polymer substrate of the coating layer within the aforementioned range, excessive pressure is prevented from being applied to a part of the separator during the lamination process, which is a process for manufacturing electrodes, thereby preventing damage to the coating layer and improving the dielectric breakdown voltage of the separator. The surface roughness of the coating layer may be controlled by adjusting the content of the first polymer binder and the average particle size ratio with inorganic particles, and the first polymer binder may be positioned between the inorganic particles on the surface of the coating layer to reduce the surface roughness.

[0068] In this specification, "surface roughness (Sa)" may mean that it was measured using Nanosystem’s Optical Profiler NV 2700.

[0069] According to one embodiment of the present invention, the first polymer binder may comprise one selected from an acrylic binder, a polyvinylidene binder, and combinations thereof. Furthermore, the first polymer binder may be a hybrid particle formed by hybridizing an acrylic binder and a polyvinylidene binder into a single particle. By selecting the first polymer binder as described above, pores in the coating layer can be formed, the binding strength of the coating layer can be improved, and the durability of the coating layer can be improved.

[0070] According to one embodiment of the present invention, the acrylic binder may be a polymer comprising a carboxylic acid ester as a repeating unit, preferably a (meth)acrylic acid ester or an acrylic-styrene copolymer.

[0071] According to one embodiment of the present invention, the (meth)acrylic acid ester (meth)acrylate methyl, (meth)acrylate ethyl, (meth)acrylate n-propyl, (meth)acrylate i-propyl, (meth)acrylate n-butyl, (meth)acrylate i-butyl, (meth)acrylate n-amyl, (meth)acrylate i-amyl, (meth)acrylate hexyl, (meth)acrylate cyclohexyl, (meth)acrylate 2-ethylhexyl, (meth)acrylate n-octyl, (meth)acrylate nonyl, (meth)acrylate decyl, (meth)acrylate hydroxymethyl, (meth)acrylate hydroxyethyl, (meth)acrylate ethylene glycol, di(meth)acrylate ethylene glycol, di(meth)acrylate propylene glycol, Examples include tri(meth)acrylate trimethylolpropane, tetra(meth)acrylate pentaerythritol, hexa(meth)acrylate dipentaerythritol, (meth)acrylate allyl, di(meth)acrylate ethylene, etc., and one or more selected from these may be used. Among these, it is preferable that one or more selected from (meth)acrylate methyl, (meth)acrylate ethyl, and (meth)acrylate 2-ethylhexyl, and it is particularly preferable that it be (meth)acrylate methyl.

[0072] According to one embodiment of the present invention, the acrylic-styrene copolymer may include an acrylic binder, and the acrylic binder may be of the polyacrylate type. For example, the binder may be one or more selected from the group consisting of styrene-butadiene rubber, nitrile-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and acrylate-based polymers, and more specifically, may be a copolymer containing acrylate.

[0073] According to one embodiment of the present invention, the polyvinylidene-based binder may be a polyvinylidene fluoride-based binder. As described above, by selecting the polyvinylidene-based binder as a polyvinylidene fluoride-based binder, the porosity of the separator can be maintained to improve the resistance of the separator, wet adhesion can be improved, and the resistance of the separator can be reduced.

[0074] According to one embodiment of the present invention, the polyvinylidene-based binder may have a hexafluoropropylene content of 15 wt% or more. Specifically, the polyvinylidene-based binder contained in the first polymer binder particles may have a hexafluoropropylene content of 10 wt% or more and 80 wt% or less, 15 wt% or more and 75 wt% or less, 20 wt% or more and 70 wt% or less, 25 wt% or more and 65 wt% or less, 30 wt% or more and 60 wt% or less, 35 wt% or more and 55 wt% or less, or 40 wt% or more and 50 wt% or less. By controlling the content of hexafluoropropylene contained in the polyvinylidene-based binder in the first polymer binder particles within the above-described range, the resistance of the separator can be reduced. The content of the hexafluoropropylene (HFP) monomer is 1 H-NMR and / or 19 It can be measured by F-NMR.

[0075] According to one embodiment of the present invention, the second polymer binder may be one selected from the group consisting of polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylamide (PAM), and combinations thereof. By selecting the second polymer binder as described above, it can be dissolved in the electrolyte to improve the porosity of the coating layer and provide pressure-dependent buffering during the lamination process, thereby preventing damage to the separator and improving the dielectric breakdown voltage.

[0076] According to one embodiment of the present invention, the average particle size (D) of the first polymer binder 50 ) may be 200 nm or more and 450 nm or less. Specifically, the average particle size (D) of the first polymer binder is 50) may be 210 nm or more and 440 nm or less, 220 nm or more and 430 nm or less, 230 nm or more and 420 nm or less, 240 nm or more and 410 nm or less, 250 nm or more and 400 nm or less, 260 nm or more and 390 nm or less, 270 nm or more and 380 nm or less, 280 nm or more and 370 nm or less, 290 nm or more and 360 nm or less, 300 nm or more and 350 nm or less, 310 nm or more and 340 nm or less, or 320 nm or more and 330 nm or less. As in the ranges described above, the average particle size (D) of the first polymer binder may be 50 By controlling the coating layer, the coating layer acts as a buffer against pressure during the lamination process before the electrolyte injection, thereby preventing damage to the separator, improving the dielectric breakdown voltage, and enabling a low surface roughness of the coating layer.

[0077] According to one embodiment of the present invention, the average particle size (D) of the inorganic particles 50 ) may be 300 nm or more and 700 nm or less. Specifically, the average particle size (D) of the inorganic particles said above. 50) is 310 nm or more and 690 nm or less, 320 nm or more and 680 nm or less, 330 nm or more and 670 nm or less, 340 nm or more and 660 nm or less, 350 nm or more and 650 nm or less, 360 nm or more and 640 nm or less, 370 nm or more and 630 nm or less, 380 nm or more and 620 nm or less, 390 nm or more and 610 nm or less, 400 nm or more and 600 nm or less, 410 nm or more and 590 nm or less, 420 nm or more and 580 nm or less, 430 nm or more and 570 nm or less, 440 nm or more and 560 nm or less, 450 nm or more and 550 nm or less, 460 nm or more and 540 nm or less, 470 nm or more and 530 nm or less, 480 nm or more and 520 nm or less, or 490 nm or more It may be 510 nm or less. The average particle size (D) of the inorganic particles within the above-mentioned range 50 By controlling ), the surface roughness of the coating layer can be lowered and the dielectric breakdown voltage can be improved.

[0078] According to one embodiment of the present invention, the weight ratio of the first polymer binder and the second polymer binder may be 5.5:4.5 to 9.5:0.5. Specifically, the weight ratio of the first polymer binder and the second polymer binder may be 5.5:4.5 to 9.5:0.5, 6.0:4.0 to 9.0:1.0, 6.5:3.5 to 8.5:1.5, or 7.0:3.0 to 8.0:2.0. By adjusting the weight ratio of the first polymer binder and the second polymer binder within the above-described range, the coating layer can provide a pressure-dependent buffering effect during the lamination process before electrolyte injection to prevent damage to the separator, thereby improving the dielectric breakdown voltage and achieving a low surface roughness of the coating layer. Additionally, by improving the porosity of the coating layer, it can provide a pressure-dependent buffering effect during the lamination process after electrolyte injection to prevent damage to the separator and improve the dielectric breakdown voltage.

[0079] According to one embodiment of the present invention, the total content of the first polymer binder and the second polymer binder may be 5 parts by weight or more and 30 parts by weight or less with respect to 100 parts by weight of the coating layer. Specifically, the total content of the first polymer binder and the second polymer binder may be 6 parts by weight or more and 29 parts by weight or less, 7 parts by weight or more and 28 parts by weight or less, 8 parts by weight or more and 27 parts by weight or less, 9 parts by weight or more and 26 parts by weight or less, 10 parts by weight or more and 25 parts by weight or less, 11 parts by weight or more and 24 parts by weight or less, 12 parts by weight or more and 23 parts by weight or less, 13 parts by weight or more and 22 parts by weight or less, 14 parts by weight or more and 21 parts by weight or less, 15 parts by weight or more and 20 parts by weight or less, 16 parts by weight or more and 19 parts by weight or less, or 17 parts by weight or more and 18 parts by weight or less, with respect to 100 parts by weight of the coating layer. By controlling the total content of the first polymer binder and the second polymer binder within the aforementioned range, the binding strength and porosity of the coating layer can be controlled.

[0080] According to one embodiment of the present invention, the content of the inorganic particles may be 70 parts by weight or more and 95 parts by weight or less with respect to 100 parts by weight of the coating layer. Specifically, the content of the inorganic particles may be 71 parts by weight or more and 94 parts by weight or less, 72 parts by weight or more and 93 parts by weight or less, 73 parts by weight or more and 92 parts by weight or less, 74 parts by weight or more and 91 parts by weight or less, 75 parts by weight or more and 90 parts by weight or less, 76 parts by weight or more and 89 parts by weight or less, 77 parts by weight or more and 88 parts by weight or less, 78 parts by weight or more and 87 parts by weight or less, 79 parts by weight or more and 86 parts by weight or less, 80 parts by weight or more and 85 parts by weight or less, 81 parts by weight or more and 84 parts by weight or less, or 82 parts by weight or more and 83 parts by weight or less, with respect to 100 parts by weight of the coating layer. By controlling the content of the inorganic particles within the aforementioned range, the heat resistance of the separation membrane can be improved.

[0081] According to one embodiment of the present invention, the inorganic particles usable in the coating layer are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles usable in one embodiment of the present invention are within the operating voltage range of the applied electrochemical element (e.g., Li / Li). + It is not particularly limited as long as oxidation and / or reduction reactions do not occur at a standard of 0 V to 5 V.

[0082] According to one embodiment of the present invention, non-limiting examples of the inorganic particles include BaTiO3, Pb(Zr,Ti)O3(PZT), and Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1, 0<y<1), Pb(Mg 1 / 3 Nb 2 / 3 Examples include O3-PbTiO3(PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc-tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), etc., and may include one or more of these.

[0083] According to one embodiment of the present invention, when pressurized for 10 seconds under conditions of 70°C and 5.2 MPa, the rate of change in thickness of the coating layer defined by the following mathematical formula 1 may be 10% or more and 25% or less.

[0084] [Mathematical Formula 1]

[0085] Thickness change rate = (Thickness of coating layer before pressurization - Thickness of separator after pressurization) / Thickness of coating layer before pressurization

[0086] Specifically, when pressurized for 10 seconds under conditions of 70 ℃ and 5.2 MPa, the thickness change rate of the coating layer defined by the above mathematical formula 1 may be 11% or more and 24% or less, 12% or more and 23% or less, 13% or more and 22% or less, 14% or more and 21% or less, 15% or more and 20% or less, 16% or more and 19% or less, or 17% or more and 18% or less. By controlling the thickness change rate of the coating layer within the above-described range, damage to the porous polymer substrate can be prevented, thereby improving the dielectric breakdown voltage.

[0087] According to one embodiment of the present invention, when impregnated for 24 hours under conditions of 25°C and 1 atmosphere in a solution comprising 70 parts by volume of ethylene carbonate and 30 parts by volume of ethylmethyl carbonate, the rate of change in the porosity of the coating layer defined by the following mathematical formula 2 may be 10% or more and 20% or less.

[0088] [Mathematical Formula 2]

[0089] Rate of change in porosity = (Porosity of coating layer after impregnation - Porosity of coating layer before impregnation) / Porosity of coating layer before impregnation

[0090] Specifically, when impregnated for 24 hours under conditions of 25°C and 1 atmosphere in a solution containing 70 parts by volume of ethylene carbonate and 30 parts by volume of ethylmethyl carbonate, the rate of change in the porosity of the coating layer defined by Equation 2 may be 11% or more and 19% or less, 12% or more and 18% or less, 13% or more and 17% or less, or 14% or more and 16% or less. By controlling the rate of change in the porosity of the coating layer within the above-described range, the surface roughness of the coating layer can be reduced, and the porosity of the coating layer can be improved to prevent uneven application of pressure and improve the dielectric breakdown voltage.

[0091] One embodiment of the present invention provides a method for manufacturing a separator for an electrochemical device, comprising the steps of: mixing a slurry for a coating layer comprising a first polymer binder in the form of particles, a second polymer binder, and inorganic particles; applying the slurry for the coating layer onto at least one surface of a porous polymer substrate; and drying the slurry for the coating layer to form a coating layer.

[0092] A method for manufacturing a separator for an electrochemical device according to one embodiment of the present invention can easily improve the dielectric breakdown voltage of the separator and prevent damage to the separator. In the description of the method for manufacturing a separator for an electrochemical device according to one embodiment of the present invention, content that overlaps with the description of the separator for an electrochemical device is omitted.

[0093] According to one embodiment of the present invention, a method for manufacturing a separator for an electrochemical device comprises the step of mixing a slurry for a coating layer comprising a first polymer binder in the form of particles, a second polymer binder, and inorganic particles. By including the step of mixing a slurry for a coating layer comprising a first polymer binder in the form of particles, a second polymer binder, and inorganic particles as described above, a coating layer can be easily formed on the separator.

[0094] According to one embodiment of the present invention, a polymer binder resin, namely a first polymer binder and a second polymer binder, may be dispersed in a suitable dispersion medium to prepare a polymer emulsion, thereby providing a slurry for a coating layer. It is preferable that the dispersion medium has a low boiling point. This is to facilitate uniform mixing and subsequent removal of the dispersion medium. Non-limiting examples of usable dispersion media include acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water, or mixtures thereof. Preferably, the dispersion medium may be water.

[0095] According to one embodiment of the present invention, a polymer binder resin, namely a first polymer binder and a second polymer binder, may be dissolved in a suitable solvent to prepare a polymer solution, thereby providing a slurry for a coating layer. It is preferable that the solvent has a solubility index similar to that of the binder polymer to be used and has a low boiling point. This is to facilitate uniform mixing and subsequent solvent removal. Non-limiting examples of usable solvents include acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water, or mixtures thereof. Preferably, the solvent may be water.

[0096] According to one embodiment of the present invention, inorganic particles may be added and dispersed in the polymer emulsion or polymer solvent. The content ratio of the inorganic particles to the polymer binders is as described above and is appropriately adjusted considering the thickness, pore size, and porosity of the coating layer according to one embodiment of the present invention that is finally manufactured.

[0097] According to one embodiment of the present invention, a method for manufacturing a separator for an electrochemical device comprises the step of applying a slurry for a coating layer onto at least one surface of a porous polymer substrate. By including the step of applying the slurry for a coating layer onto at least one surface of a porous polymer substrate as described above, a coating layer can be formed in a single application. Furthermore, due to the separation between inorganic particles and polymer binders in the slurry for the coating layer, an excess of inorganic particles exists in the portion close to the porous polymer substrate, and an excess of polymer binder particles exists in the portion far from the porous polymer substrate, thereby improving adhesion to the electrode and improving the porosity of the separator.

[0098] According to one embodiment of the present invention, the method of applying the slurry for the coating layer to the surface of a porous polymer substrate is not specifically limited to any one method, and conventional methods known in the art may be used. For example, various methods such as dip coating, die coating, roll coating, comma coating, or a combination thereof may be used.

[0099] According to one embodiment of the present invention, a method for manufacturing a separator for an electrochemical device comprises the step of drying a slurry for a coating layer to form a coating layer. By including the step of drying a slurry for a coating layer to form a coating layer as described above, damage to the coating layer can be minimized, and a dispersion medium or solvent contained in the slurry can be easily removed.

[0100] According to one embodiment of the present invention, the drying process appropriately sets time conditions to minimize the occurrence of surface defects in the coating layer. In the drying process, a drying aid such as a drying oven or hot air may be used within an appropriate range.

[0101] According to one embodiment of the present invention, the separator is interposed between the cathode and the anode and is manufactured into an electrode assembly by a lamination process in which heat and / or pressure is applied to bond them. In one embodiment of the present invention, the lamination process may be performed by a roll press device comprising a pair of pressure rollers. That is, the cathode, the separator, and the anode may be sequentially stacked and placed between the pressure rollers to achieve interlayer bonding. At this time, the lamination process may be performed by a hot pressing method.

[0102] One embodiment of the present invention provides an electrochemical device comprising: an anode (300); a cathode (500); and a separator (100) interposed between the anode (300) and the cathode (500).

[0103] An electrochemical device according to one embodiment of the present invention can reduce the short circuit failure rate and the low voltage failure rate, and can improve the dielectric breakdown voltage.

[0104] FIG. 2 is a schematic diagram of an electrochemical device according to one embodiment of the present invention. An electrochemical device according to one embodiment of the present invention will be described in detail with reference to FIG. 2.

[0105] In the present invention, the electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and is a concept that encompasses primary batteries and secondary batteries. In this specification, the secondary battery is capable of charging and discharging and refers to a lithium secondary battery, a nickel-cadmium battery, a nickel-hydrogen battery, etc. The lithium secondary battery uses lithium ions as an ion conductor, and examples include a non-aqueous electrolyte secondary battery containing a liquid electrolyte, an all-solid-state battery containing a solid electrolyte, a lithium polymer battery containing a gel polymer electrolyte, and a lithium metal battery using lithium metal as a negative electrode, but are not limited thereto.

[0106] According to one embodiment of the present invention, the positive electrode (300) comprises a positive electrode current collector and a positive electrode active material layer comprising a positive electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. The positive electrode active material is a layered compound such as a lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-x M x Ni-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x = 0.01 ~ 0.3); chemical formula LiMn1-xM xIt may include a lithium manganese complex oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of the Li of the chemical formula is substituted with alkaline earth metal ions; a disulfide compound; and one or more of Fe2(MoO4)3.

[0107] According to one embodiment of the present invention, the cathode (500) comprises a cathode current collector and a cathode active material layer comprising a cathode active material, a conductive material, and a binder resin on at least one surface of the current collector. The cathode comprises, as the cathode active material, carbon such as lithium metal oxide, non-graphitizable carbon, or graphite-based carbon; LixFe2O3 (0≤x≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, 2, and 3 elements of the periodic table, halogens; 0 <x≤1; 1≤y≤3; 1≤z≤8) 등의 금속 복합 산화물; 리튬 금속; 리튬 합금; 규소계 합금; 주석계 합금; SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, 및 Bi2O5등의 금속 산화물; 폴리아세틸렌 등의 도전성 고분자; Li-Co-Ni 계 재료; 티타늄 산화물 중 선택된 1종 또는 2종 이상의 혼합물을 포함할 수 있다.

[0108] According to one embodiment of the present invention, the conductive material may be, for example, any one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon, and polyphenylene derivative, or a mixture of two or more of these conductive materials. More specifically, it may be one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.

[0109] According to one embodiment of the present invention, the current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used.

[0110] According to one embodiment of the present invention, the binder resin may be a polymer commonly used in the industry for electrodes. Non-limiting examples of such binder resins include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-cotrichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Examples include acetatepropionate), cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methyl cellulose, but are not limited thereto.

[0111] In the present invention, the anode slurry for manufacturing the anode active material layer may include a dispersant, and the dispersant may be a pyrrolidone-based compound. Specifically, it may be N-methylpyrrolidone (N-methylpyrrolidone, ADC-01, LG Chem).

[0112] According to one embodiment of the present invention, the content of the dispersant included in the anode slurry may be greater than 0 parts by weight and less than or equal to 0.5 parts by weight per 100 parts by weight of the anode slurry. Specifically, the content of the dispersant included in the anode slurry may be greater than 0.05 parts by weight and less than or equal to 0.4 parts by weight per 100 parts by weight of the anode slurry.

[0113] According to one embodiment of the present invention, the cathode slurry for manufacturing the cathode active material layer may include a dispersant, and the dispersant may be a polypyrrolidone-based compound. Specifically, the dispersant may be polyvinylpyrrolidone (Polyvinylpyrrolidone, Junsei Corporation, Japan).

[0114] According to one embodiment of the present invention, the content of the dispersant included in the cathode slurry may be greater than 0 parts by weight and less than or equal to 0.5 parts by weight per 100 parts by weight of the cathode slurry. Specifically, the content of the dispersant included in the cathode slurry may be greater than 0.05 parts by weight and less than or equal to 0.4 parts by weight per 100 parts by weight of the cathode slurry.

[0115] According to one embodiment of the present invention, an electrode assembly prepared as above can be loaded into a suitable case and an electrolyte injected to manufacture an electrochemical device.

[0116] According to one embodiment of the present invention, the electrolyte is A + B - As a salt with a structure like that, A + is Li + , Na + , K +It includes alkali metal cations such as or ions composed of combinations thereof, and B - is PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - Salts containing anions such as or combinations thereof are dissolved or dissociated in organic solvents composed of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethylmethyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or mixtures thereof, but are not limited thereto.

[0117] One embodiment of the present invention provides a battery module including a battery including the electrochemical element as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool that moves by receiving power from a battery motor; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc.; an electric two-wheeled vehicle including an electric bicycle (E-bike) and an electric scooter (E-scooter); an electric golf cart; and a power storage system.

[0119] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0120] <Example 1>

[0121] A polyethylene resin (weight-average molecular weight 900,000) was extruded, and a porous polymer substrate (total thickness about 9 μm, porosity 40 volume%) was prepared by a wet method.

[0122] As the first polymer binder, styrene-butyl acrylate (LG Chem, particle size: 400 nm), an acrylic binder, and as the first polymer binder, a copolymer of PVdF and HFP with a degree of substitution (weight ratio of HFP in the PVdF-based polymer) of 5 wt% (Arkema, particle size: 250 nm) were used. As the second polymer binder, acrylic acid (Lubrizol, Ck702) was used. The inorganic particles were Al2O 3( Particle size 500 nm) was used.

[0123] A slurry for a coating layer (solid content concentration: 30 wt%) was prepared by dispersing the first polymer binder, the second polymer binder, and the inorganic particles in water. The weight ratio of the first polymer binder to the second polymer binder was added at 9:1, and the particle size (D) of the first polymer binder and the inorganic particles 50 The ratio of ) was 1:1. Furthermore, the weight of the first polymer binder and the second polymer binder was 20% by weight relative to the total weight of the first polymer binder, the second polymer binder, and the inorganic particles.

[0124] A separation membrane was prepared by applying the dispersion to both sides of the surface of the porous polymer substrate using a doctor blade in a bar coating method and drying it with a heat gun at 50°C.

[0125] <Example 2>

[0126] A separation membrane was prepared in the same manner as in Example 1, except that a slurry for a coating layer was prepared by adding the first polymer binder and the second polymer binder in a weight ratio of 7:3.

[0127] <Example 3>

[0128] In Example 1 above, the particle size (D) of the first polymer binder and the inorganic particles 50 A separation membrane was prepared in the same manner as in Example 1, except that the ratio of the first polymer binder and the second polymer binder were changed to 1:3 and the weight ratio of the first polymer binder and the second polymer binder was added at 7:3 to prepare a slurry for a coating layer.

[0129] <Comparative Example 1>

[0130] A separation membrane was prepared in the same manner as in Example 1, except that a second polymer binder was used instead of the first polymer binder in Example 1.

[0131] <Comparative Example 2>

[0132] In Example 1 above, the particle size (D) of the first polymer binder and the inorganic particles 50 A separation membrane was prepared in the same manner as in Example 1, except that the ratio of the first polymer binder and the second polymer binder were changed to 1:10 and the weight ratio of the first polymer binder and the second polymer binder was added at 5:5 to prepare a slurry for a coating layer.

[0133] <Comparative Example 3>

[0134] In Example 1 above, the particle size (D) of the first polymer binder and the inorganic particles 50A separation membrane was prepared in the same manner as in Example 1, except that the ratio of ) was changed to 1:10 and the first polymer binder was used instead of the second polymer binder.

[0135] <Comparative Example 4>

[0136] A separation membrane was prepared in the same manner as in Example 1, except that a slurry for a coating layer was prepared by adding the first polymer binder and the second polymer binder in a weight ratio of 5:5.

[0137] <Comparative Example 5>

[0138] A separation membrane was prepared in the same manner as in Example 1, except that the first polymer binder was used instead of the second polymer binder in Example 1.

[0139] <Comparative Example 6>

[0140] A separation membrane was prepared in the same manner as in Example 1, except that a slurry for a coating layer was prepared by adding the first polymer binder and the second polymer binder in a weight ratio of 3:7.

[0141] <Comparative Example 7>

[0142] In Example 1 above, the particle size (D) of the first polymer binder and the inorganic particles 50 A separator was prepared in the same manner as in Example 1 above, except that the ratio of ) was changed to 1:0.5.

[0144] Table 1 below shows the ratio of particle sizes of the first polymer binder and the second polymer binder and the weight ratio of the first polymer binder and the second polymer binder of Examples 1 to 3 and Comparative Examples 1 to 7.

[0145] Ratio of particle sizes of the first polymer binder and the second polymer binder Weight ratio of the first polymer binder and the second polymer binder First polymer binder inorganic particles First polymer binder Second polymer binder Example 1 1 1 9 1 Example 2 1 1 7 3 Example 3 1 3 7 3 Comparative Example 1 - - - 10 Comparative Example 2 1 10 5 5 Comparative Example 3 1 10 10 - Comparative Example 4 1 1 5 5 Comparative Example 5 1 1 10 - Comparative Example 6 1 1 3 7 Comparative Example 7 1 0.5 9 1

[0146] Manufacture of Electrochemical Devices

[0147] 1) Manufacture of the anode

[0148] Cathode active material (LiNi 0.8 Mn 0.1 Co 0.1 O2), a conductive material (carbon black), a dispersant (N-methylpyrrolidone, ADC-01, LG Chem), and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for an anode active material layer with a concentration of 50 wt% of the components excluding water. Next, the slurry was applied to the surface of an aluminum thin film (thickness 10 μm) and dried to produce an anode having an anode active material layer (thickness 120 μm).

[0149] 2) Preparation of the cathode

[0150] Graphite (a blend of natural graphite and artificial graphite), a conductive material (carbon black), a dispersant (Polyvinylpyrrolidone, Junsei, Japan), and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a negative electrode active material layer with a concentration of 50 wt% of the components excluding water. Next, the slurry was applied to the surface of a copper thin film (thickness 10 μm) and dried to manufacture a negative electrode having a negative electrode active material layer (thickness 120 μm).

[0151] 3) Lamination Process

[0152] An electrode assembly was obtained by interposing the separator of the example and comparative example between the cathode and anode manufactured above, laminating them, and performing a lamination process. The lamination process was performed using a hot press for 10 seconds under conditions of 70°C and 5.2 MPa.

[0154] <Experimental Example 1: Measurement of Surface Roughness of Coating Layer>

[0155] Measurements were taken using the Optical Profiler NV 2700 from Nanosystem. The surface of the coating layer was set as the measurement surface and the sample stage was configured. Average values ​​were calculated from four different measurement areas, and the conditions were set as follows.

[0156] Cutoff: 0.8 mm, Scan speed: 0.1 mm / s, Magnification: 500x

[0157] <Experimental Example 2: Measurement of the Rate of Change in Coating Layer Thickness>

[0158] The rate of change in thickness of the separator membranes of Examples 1 to 3 and Comparative Examples 1 to 7 before and after pressurizing for 10 seconds under conditions of 70°C and 5.2 MPa was calculated using the following Equation 1.

[0159] [Mathematical Formula 1]

[0160] Thickness change rate = (Thickness of coating layer before pressurization - Thickness of coating layer after pressurization) / Thickness of coating layer before pressurization

[0161] <Experimental Example 3: Measurement of Short Circuit Defect Rate>

[0162] For Examples 1 to 3 and Comparative Examples 1 to 7, 100 specimens were prepared for each, and their dielectric breakdown characteristics were evaluated. The dielectric breakdown voltage was measured using an AC / DC / IR Hi-Pot tester. The separator membranes of each example and comparative example were placed between an aluminum bottom plate jig and a cylindrical electrode rod, and the DC current was set to 0.5 mA and the voltage to 100 V / s (voltage 3 kV, ramp-up time 30 s). When the experiment began, the voltage rose, and the measurement was completed when a short circuit occurred; the voltage at that point was measured as the dielectric breakdown voltage. The evaluation of the short-circuit failure rate (short-circuit occurrence rate or Hi-Pot failure rate) was based on 75 V, and the percentage of specimens that experienced a short circuit under conditions of 75 V or lower was calculated out of the total number of specimens tested.

[0163] <Experimental Example 4: Determination of the Rate of Change in Porosity of the Coating Layer>

[0164] The porosity of the membranes of Examples 1 to 3 and Comparative Examples 1 to 7 was determined before and after impregnation in a solution containing 70 parts by volume of ethylene carbonate and 30 parts by volume of ethylmethyl carbonate for 24 hours under conditions of 25°C and 1 atm, and the rate of change in porosity of the coating layer was measured using the following Equation 2.

[0165] [Mathematical Formula 2]

[0166] Rate of change in porosity = (Porosity of coating layer after impregnation - Porosity of coating layer before impregnation) / Porosity of coating layer before impregnation

[0167] The above porosity was calculated using the following [Equation 3] and [Equation 4].

[0168] [Mathematical Formula 3]

[0169] Porosity (Volume %) = {1 - (Apparent Density / True Density)} × 100

[0170] [Mathematical Formula 4]

[0171] Apparent density (g / cm³) 3 )= {Weight of coating layer [g] / Thickness of coating layer [cm] × Area of ​​coating layer [cm²] 2 ])}

[0172] Three samples measuring 5 cm in the MD / TD direction were obtained from the coating layers of each example and comparative example. The thickness of the coating layer was determined by taking the average value after measuring at 5 points for each sample, and the weight of each sample was measured using a balance. The average value of the three samples was calculated and introduced into Equations 3 and 4 to calculate the porosity. Meanwhile, the true density of each sample was applied based on theoretically verified values, such as the molecular weight of each applied component.

[0173] <Experimental Example 5: Measurement of Wet Adhesion>

[0174] The separators of Examples 1 to 3 and Comparative Examples 1 to 7 were cut to a length of 70 mm x 20 mm, and specimens were fabricated by laminating the prepared electrodes and separators using a press under conditions of 60°C, 6.5 MPa, and 1 sec. The prepared specimens were placed in a battery case along with an electrolyte and maintained for 4 hours to impregnate the specimens with the electrolyte. The electrolyte used was prepared by mixing ethylene carbonate and ethylmethylate in a volume ratio of 7:3 and having a concentration of LiPF61M. Afterward, the specimens were removed from the case and fixed by attaching them to a glass plate using double-sided tape, with the electrodes positioned to face the glass plate. The separator portion of the specimen was peeled off at 25°C at a speed of 200 mm / min at a 90° angle, and the strength of the positive and negative electrodes at this time was measured.

[0175] <Experimental Example 6: Measurement of Low Voltage Defect Rate>

[0176] After manufacturing, batteries undergo an activation process to ensure stable charging and discharging. The activation process involves charging, discharging, and storing the battery at high or room temperature for a certain period.

[0177] After a certain period, the voltage of the battery drops, and the standard deviation (σ) of the voltage dispersion is calculated. Depending on the battery design, batteries exceeding the constant * σ (the constant is 0.5 to 3) are classified as defective.

[0178] The battery containing the separator of Examples 1 to 3 and Comparative Examples 1 to 7 was charged with a constant current (CC) of 0.05C until it reached 4.25V, and then charged with a constant voltage until it reached 0.01C. Afterward, the voltage of the battery according to the activation process was measured.

[0179] The dispersion of the voltage of batteries produced at the same point in time was measured by multiplying the standard deviation by 0.5, and batteries deviating from this were identified as defective.

[0180] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Surface roughness (Sa, μm) 0.097 0.112 0.162 0.256 0.213 0.221 0.123 0.114 0.121 0.085 Coating layer thickness change rate (%) 24 20 17 5 7 15 10 27 8 10 Short circuit defect rate (%) 2 3 2 35 33 24 7 3 15 20 Rate of change in porosity (%) 10 14 15 37 25 5 13 4 20 4 Wet adhesion (gf / 20mm) 7 6 7 15 2 1 2 12 3 7 Low voltage failure rate (%) 5 3 3 21 5 29 3 18 2 10

[0181] Referring to Table 2 above, it was confirmed that Examples 1 to 3 according to one embodiment of the present invention achieve a low surface roughness of the coating layer, satisfy the particle size ratio, and satisfy the weight ratio of the polymer binder, thereby achieving a low short circuit defect rate and a low voltage defect rate.

[0182] In this regard, it was confirmed that Comparative Examples 1 to 3, which have a high surface roughness of the coating layer, showed an increase in the short circuit failure rate and / or low voltage failure rate, while Comparative Examples 4 and 5, which have a low content of the first polymer binder, showed a decrease in wet adhesion or an increase in the low voltage failure rate. Furthermore, it was confirmed that Comparative Example 6, which contains an excessive amount of the second polymer binder, showed an increase in the short circuit failure rate, an increase in the rate of change in porosity, and a decrease in wet adhesion. Additionally, it was confirmed that Comparative Example 7 showed an increase in the short circuit failure rate and / or low voltage failure rate.

[0183] Accordingly, a separator for an electrochemical device, which is an embodiment of the present invention, controls the ratio of the average particle size of a particulate first polymer binder and an inorganic particle included in the coating layer, and controls the ratio of the content of the first polymer binder and the second polymer binder to reduce the surface roughness of the coating layer, while simultaneously preventing damage occurring during the lamination process, which is a manufacturing process of the electrochemical device, and improving the dielectric breakdown voltage of the electrochemical device. Explanation of the symbols

[0184] 100: Separator for electrochemical devices 110: Porous polymer substrate 130: Coating layer 300: Anode 500: Cathode

Claims

Claim 1 A separator for an electrochemical device comprising: a porous polymer substrate; and a coating layer provided on at least one surface of the porous polymer substrate and comprising a particulate first polymer binder, a second polymer binder, and inorganic particles, wherein the second polymer binder is a soluble polymer binder, the ratio of the average particle size (D50) of the first polymer binder to the average particle size (D50) of the inorganic particles is 1:1 to 1:5, the weight of the first polymer binder included in the coating layer is greater than the weight of the second polymer binder, the weight ratio of the first polymer binder to the second polymer binder is 5.5:4.5 to 9.5:0.5, and the surface roughness (Sa) of the surface opposite to the surface adjacent to the porous polymer substrate of the coating layer is 0.20 μm or less. Claim 2 delete Claim 3 A separator for an electrochemical device according to claim 1, wherein the first polymer binder comprises one selected from an acrylic binder, a polyvinylidene binder, and a combination thereof. Claim 4 A separator for an electrochemical device according to claim 1, wherein the second polymer binder is one selected from the group consisting of polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylamide (PAM), and combinations thereof. Claim 5 In claim 1, the average particle size (D) of the first polymer binder 50 ) is a separator for an electrochemical device having a diameter of 200 nm or more and 450 nm or less. Claim 6 In claim 1, the average particle size (D) of the inorganic particles 50 ) is a separator for an electrochemical device having a thickness of 300 nm or more and 700 nm or less. Claim 7 delete Claim 8 A separator for an electrochemical device according to claim 1, wherein the total content of the first polymer binder and the second polymer binder is 10 parts by weight or more and 20 parts by weight or less per 100 parts by weight of the coating layer. Claim 9 A separator for an electrochemical device according to claim 1, wherein when pressurized for 10 seconds under conditions of 70 ℃ and 5.2 MPa, the thickness change rate of the coating layer defined by the following mathematical formula 1 is 10% or more and 25% or less: [Mathematical Formula 1] Thickness change rate = (Thickness of coating layer before pressurization - Thickness of coating layer after pressurization) / Thickness of coating layer before pressurization. Claim 10 A separator for an electrochemical device according to claim 1, wherein when impregnated for 24 hours under conditions of 25°C and 1 atm in a solution comprising 70 parts by volume of ethylene carbonate and 30 parts by volume of ethyl methyl carbonate, the rate of change in porosity of the coating layer defined by the following Equation 2 is 10% or more and 20% or less: [Equation 2] Rate of change in porosity = (Porosity of coating layer after impregnation - Porosity of coating layer before impregnation) / Porosity of coating layer before impregnation. Claim 11 An electrochemical device comprising: an anode; a cathode; and a separator interposed between the anode and the cathode, which is any one of claims 1, 3 to 6 and 8 to 10.

Citation Information

Patent Citations

  • Separator for lithium secondary battery, lithium secondary battery including the same, and method of preparing the separator for lithium secondary battery

    KR1020220143465A

  • Separator for secondary battery

    KR1020230044951A